Creative formations in honorable prophetic decoration lines (Al-Academy, 2018)
The Islamic art is filled with precious and holiness contents for what it carries of spiritual meanings represented by the Holy Quran, Hadith and texts which inspired the Calligrapher fertile imagination draw from it a wide space for holiness and spiritual expression with artistic explanation of aesthetic and decorative nature, its issuance pivots depended on decoration and calligraphy elements. The main elements which enriched the aesthetic and expressional side are the texts which used by the Calligraphers whom tried to be perfect and creative by presentation techniques and issuance treatments hold within the beauty of the shape and content. The most remarkable artistic achievements are honorable prophetic decoration for what it has of holiness content and religious symbol represented by the personality of the honorable prophet Mohammed (God peace upon him and his household), for this reason , the Calligraphers compete in issuance and artistic perfection of honorable prophetic decoration lines in shape varieties with indicative and aesthetic dimensions. For what the honorable prophetic decoration content has of specialty at the Calligraphers, they tried to employ its features of items and meanings which helped in produce creations with variety artistic works mixed between the holiness, aesthetic and expression side with creative issuance treatment, the Calligrapher try his best depending of what he represent of his skill and his perfect of handwritten and issuance of decoration paint map which inspired from it text meanings creative ideas within the shape organizations and variety areal partitions, so the researcher depend in his study on four chapters:The first chapter includes the study problem, its importance, its goals, its limits and terms definitions which the study deals with it , while the second chapter includes main pivots : origin of honorable prophetic decoration within consecutive time periods , also include the creative kinds of honorable prophetic decoration corresponding to shape varieties and various works , the researcher deal with creation elements and it role in create a new creative shapes and also formalism eloquence which included decoration text meanings and handwritten formations in honorable prophetic decoration. The third chapter includes analysis two samples of creative shape in its design and build up a general map for the samples and the fourth chapter includes the study results